2004
DOI: 10.1182/blood.v104.11.4039.4039
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of the Antiphospholipid Syndrome in Patients with Malignancies.

Abstract: The presence of antiphospholipid antibodies has been reported in a large variety of malignancies. It is not clear, however, if the antiphospholipid antibodies are related to thrombotic associations of the antiphospholipid syndrome (APS) in these patients. We investigated the frequency of thrombotic manifestations in 58 patients with the presence of antiphospholipid antibodies and a history of neoplasia, including haematologic and lymphoproliferative malignancies. Methods Antiphospholipid antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The pooled prevalence rates of the various types of cancer ranged between 7% and 28% for aCL antibodies, 19,[24][25][26][27][28][29][30][31][32][40][41][42][43][44][45][46][47][48][49][50] between 5% and 53% for anti-b2-GPI antibodies, [24][25][26]33,40,42,44,45,51,52 and from 3% to 80% for LA. [23][24][25]32,45,49,50,53,54 Two studies examined all 3 aPL antibodies, but none of them reported the percentage of patients who were positive for all 3; therefore, the pooled prevalence rate of triplepositive aPL antibodies could not be determined. 24,25 Ten additional studies evaluated the presence of aPL antibodies in different cancer types but did not specify the antibody subtype.…”
Section: Pooled Prevalence Rates Of Developing Apl Antibodies In Patients With Solid Tumors (31 Studies)mentioning
confidence: 99%
“…The pooled prevalence rates of the various types of cancer ranged between 7% and 28% for aCL antibodies, 19,[24][25][26][27][28][29][30][31][32][40][41][42][43][44][45][46][47][48][49][50] between 5% and 53% for anti-b2-GPI antibodies, [24][25][26]33,40,42,44,45,51,52 and from 3% to 80% for LA. [23][24][25]32,45,49,50,53,54 Two studies examined all 3 aPL antibodies, but none of them reported the percentage of patients who were positive for all 3; therefore, the pooled prevalence rate of triplepositive aPL antibodies could not be determined. 24,25 Ten additional studies evaluated the presence of aPL antibodies in different cancer types but did not specify the antibody subtype.…”
Section: Pooled Prevalence Rates Of Developing Apl Antibodies In Patients With Solid Tumors (31 Studies)mentioning
confidence: 99%